Outcome Terapi Covid-19 pada Pasien yang Mendapatkan Antikoagulan Profilaksis di RSPAL Dr. Ramelan Surabaya: Outcome Covid-19 Anticoagulant Prophylaxis in Covid-19 Patients at Dr. Ramelan Naval Center Hospital Surabaya - Rizki Damayanti; Anita Purnamayanti; Aguslina Kirtishanti; Ediyono Ediyono (Jurnal Surya Medika (JSM), 2022)
Complications of thrombotic and hemorrhagic coagulation often occur in Covid-19 patients, so it is advisable to provide anticoagulant therapy, accompanied by monitoring of parameters of coagulation abnormalities, including D-Dimer. This study aims to determine the outcome of therapy for Covid-19 in patients with anticoagulant prophylaxis use in RSPAL Dr. Ramelan Surabaya. This study is a retrospective descriptive study based on medical records of Covid-19 patients from June-August 2021. The sample in this study was subjects aged >18 years who were confirmed positive for Covid-19 based on RT-PCR, with comorbid or without comorbidities, and received anticoagulant therapy. Then, this study did not include subjects who were pregnant or with malignancy/acute conditions. From 134 research samples, it was found that the use of anticoagulants using a single anticoagulant (n=131, 97.76%) was more widely used, with the most frequently used types being enoxaparin (n=68, 50.75%), and heparin (n=48, 35,8%). In conclusion, the recovery percentage in Covid-19 subjects with anticoagulant therapy was 77.61%, and the percentage of mortality was 22,39%.